2020
DOI: 10.1186/s13054-020-02865-y
|View full text |Cite
|
Sign up to set email alerts
|

Success and complications by team composition for prehospital paediatric intubation: a systematic review and meta-analysis

Abstract: Background: Clinical team composition for prehospital paediatric intubation may affect success and complication rates. We performed a systematic review and meta-analysis to determine the success and complication rates by type of clinical team. Methods: We searched MEDLINE, EMBASE, and CINAHL for interventional and observational studies describing prehospital intubation attempts in children with overall success, first-pass success, and complication rates. Eligible studies, data extraction, and assessment of ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 53 publications
6
21
0
2
Order By: Relevance
“…Wir haben in unsere Analyse eine Leitlinie aufgenommen [ 24 ], 3 SR [ 148 150 ], 9 narrative Reviews [ 151 159 ], 2 RCT [ 160 , 161 ] und 27 Beobachtungsstudien (Anhang RR 4.1; [ 162 188 ]).…”
Section: Evidenzen Für Die Leitlinienunclassified
“…Wir haben in unsere Analyse eine Leitlinie aufgenommen [ 24 ], 3 SR [ 148 150 ], 9 narrative Reviews [ 151 159 ], 2 RCT [ 160 , 161 ] und 27 Beobachtungsstudien (Anhang RR 4.1; [ 162 188 ]).…”
Section: Evidenzen Für Die Leitlinienunclassified
“…To the Editor, Garner et al [1] reported that physician teams had higher rates of pediatric intubation success and lower rates of overall airway complications than other team types and that prehospital teams including physicians should be mobilized whenever practicable for critically ill children requiring prehospital intubation.…”
Section: Romain Jouffroy Stéphanie Fogel Peter Jones and Benoît Vivmentioning
confidence: 99%
“…Third, from a methodological point of view, we wonder why the authors did not consider an alternative group of physicians who do not use muscle relaxants. Indeed, emergency services traditionally intubate children without muscle relaxants [1], and the results of Garner et al strongly suggest an effect of muscle relaxants on outcomes, whoever the operator. Fourth, the wide age range used for pediatric definition possibly influences the results because airway access conditions vary greatly between infancy and adolescence.…”
Section: Romain Jouffroy Stéphanie Fogel Peter Jones and Benoît Vivmentioning
confidence: 99%
“…Children constitute roughly only five percent of the caseload of Emergency Medical Services (EMS), with an incidence of prehospital TI of 0.1% to 5.0% in those pediatric patients. 6 Unsurprisingly, studies confirm increased rates of TI failure and complications in pediatric patients. 6,7 Authors conclude that specialist competence in pediatric advanced airway management is crucial.…”
Section: Introductionmentioning
confidence: 98%
“…6 Unsurprisingly, studies confirm increased rates of TI failure and complications in pediatric patients. 6,7 Authors conclude that specialist competence in pediatric advanced airway management is crucial. 1,2,[7][8][9] Research into pediatric prehospital airway management is considered a prioritized research area.…”
Section: Introductionmentioning
confidence: 98%